2022
DOI: 10.1039/d2sm01055k
|View full text |Cite
|
Sign up to set email alerts
|

Atypical vesicles and membranes with monolayer and multilayer structures formed by graft copolymers with diblock side-chains: nonlamellar structures and curvature-enhanced permeability

Abstract: Graft copolymers with diblock side-chains Am(-graft-B3Ay)n in a selective solvent have been reported to self-assemble into vesicles, but the structure is expected to differ distinctly from lipid bilayers. Surprisingly, the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…Core–shell bottle-brush copolymers with diblock side chains have emerged as a focal point in the study of polymer aggregates. These copolymers can generate well-defined individual nanoparticles such as spherical and cylinder micelles, worm-like micelles, , and monolayer and multilayer vesicles . Additionally, it has been demonstrated that these copolymers can assemble strung micelles with increased backbone rigidity. Our previous study revealed that stable single or strung micelles could be obtained separately by adjusting the architectural parameters of core–shell bottle-brush copolymers .…”
Section: Introductionmentioning
confidence: 99%
“…Core–shell bottle-brush copolymers with diblock side chains have emerged as a focal point in the study of polymer aggregates. These copolymers can generate well-defined individual nanoparticles such as spherical and cylinder micelles, worm-like micelles, , and monolayer and multilayer vesicles . Additionally, it has been demonstrated that these copolymers can assemble strung micelles with increased backbone rigidity. Our previous study revealed that stable single or strung micelles could be obtained separately by adjusting the architectural parameters of core–shell bottle-brush copolymers .…”
Section: Introductionmentioning
confidence: 99%
“…The self-assembly of this functional polymer allows creation of compartmentalized macromolecules and assembly of them into supramolecular multicompartmentalized structures. Driven by the intermolecular interactions between hydrophilic/hydrophobic blocks on the pendent chains, the aggregation of bottlebrush polymers generates a wide range of multifunctional structures from nanoparticles exhibiting well defined linear compartments to microparticles and percolated polymer networks presenting granular inner structures …”
mentioning
confidence: 99%
“…Driven by the intermolecular interactions between hydrophilic/hydrophobic blocks on the pendent chains, the aggregation of bottlebrush polymers generates a wide range of multifunctional structures from nanoparticles exhibiting well defined linear compartments to microparticles and percolated polymer networks presenting granular inner structures. 17 Core−shell bottlebrush polymers with pendent chains of poly(D,L-lactic acid)-block-poly(2-methacryloyloxyethyl phosphorylcholine) (PLA-b-PMPC) amphiphilic "AB" diblock copolymers grafted on a poly(2-hydroxyethyl methacrylate (HEMA)-co-methyl methacrylate (MMA) backbone were produced via the "grafting from" approach (Scheme 1). The core−shell bottlebrush polymer was obtained in five synthetic steps combining ATRP, ROP, and postmodification techniques.…”
mentioning
confidence: 99%